Takwīn al-Bīah al-Lughawiyyah Litarqiyah al-Mahārah al-Intājiyyah fī al-Ma’āhid al-‘Aṣriyyah bi Ponorogo - Moh. Munir; Rizka Eliyana Maslihah (LISANIA: Journal of Arabic Education and Literature, 2021)
This qualitative research aimed to find out: 1) the formation of formal and natural language environment to improve students' speaking skills in various modern Islamic boarding Schools at Ponorogo. 2) the formation of formal and natural language environment to improve students' writing skills in various Modern Islamic Boarding Schools at Ponorogo. The results indicate that: 1) Students' speaking skills are improved through the following Arabic language environmental activities: using Arabic in daily conversation, Arabic learning, the use of language laboratory, adding new daily vocabulary, annual language competition, listening to foreign language news, language error correction, speech competition, poetry reading, debate, and Arabic storytelling. 2) Students' writing skills are improved through the following Arabic language environmental activities: writing foreign-language articles, speeches, debate, English storytelling, poetry, songs, drama texts, and Arabic news texts, weekly writing exercises, and writing Arabic articles competition.